Sustained attention in adult ADHD: time-on-task effects of various measures of attention - Tucha, Lara; Weisbrod, Matthias (Journal of neural transmission, 2017)
Neuropsychological research on adults with ADHD showed deficits in various aspects of attention. However, the majority of studies failed to explore the change of performance over time, so-called time-on-task effects. As a consequence, little is known about sustained attention performance of adults with ADHD. The aim of the present study was therefore to test the hypothesis of sustained attention deficits of adults with ADHD. Twenty-nine adults with ADHD and 30 healthy individuals were assessed on four 20-min tests of sustained attention, measuring alertness, selective attention, divided attention and flexibility. The deterioration of performance over time (time-on-task effects) was compared between patients with ADHD and healthy individuals to conclude on sustained attention performance. Compared to healthy individuals, patients with ADHD showed significant deficits of medium size in selective attention and divided attention. Furthermore, medium sustained attention deficits was observed in measures of alertness, selective attention and divided attention. This study supports the notion of sustained attention deficits of adults with ADHD.